Contribution of Tree Legumes in the Production Dynamics of Yellow Yam (Dioscorea cayenensis Lam) in the South Cameroon Plateau - Djakou, Guy Aurélien Nganso; Tonfack, Libert Brice; Magaptche, Eddy Léonard Ngonkeu; Youmbi, Emmanuel (International Journal of Environment, Agriculture and Biotechnology, 2023)
The overexploitation of agricultural soils as a result of the increased need for food by local populations is leading to serious dysfunctions in land restoration. These dysfunctions, aggravated by climate change, require the implementation of ecological engineering strategies to rehabilitate the soil. The soils of the South Cameroonian plateau suffer significant degradation in terms of loss of fertilizing elements due to extensive agricultural practices, which limits agricultural production. This work showed how tree legumes contribute to improving the yield of yellow yam (Dioscorea cayenensis) in the South Cameroonian plateau, to ultimately support the production of agroecosystems in this environment. Within the framework of this study, an experimental set-up was designed to measure the performance of tree legumes in the field. The experimental set-up is a randomized complete block trial with three treatments and three replications on 3000 m2. The control plot without shrubs, the plot with Calliandra, and the plot with Senna. This trial was carried out in the district of Mbankomo, Mefou, and Akono Department, Central Region. After monitoring the experiment, it was found that Senna spectabilis produced more nutrients than Calliandra calothyrsus. Thus, each Senna shrub produced 1.54 kg of litter in the first year and 2.04 kg in the second year for a quantity of nitrogen of 192.76 kg/ha and 260 kg/ha respectively in the first and second year. Each Calliandra shrub produced 1.46 kg and 1.87 kg of litter for a nutrient amount of 183 kg/ha and 236.81 kg/ha of nitrogen during the two years of the experiment. The combination of tree legumes and field crops increased yam yields by a factor of 2 or 3 compared to traditional agriculture. The growth rate of the yam is accelerated as well as its vegetative cycle, which is reduced from 7.5 months to 6 months as a result of the increase in soil organic matter through the shrub legume litter. Agroforestry practices could have a positive impact on soil characteristics and microbial communities, resulting in enhanced soil fertility and long-term sustainability of agricultural production. According to the results obtained, the insertion of tree legumes in agrosystems is a more efficient and less costly way to gradually and sustainably increase nitrogen availability and soil fertility.